Toxic Chemicals and Persistent Organic Pollutants Associated with Micro-and Nanoplastics Pollution - Charles Obinwanne Okoye; Charles Izuma Addey; Olayinka Oderinde; Joseph Onyekwere Okoro; Jean Yves Uwamungu; Chukwudozie Kingsley Ikechukwu; Emmanuel Sunday Okeke; Onome Ejeromedoghene; Elijah Chibueze Odii (Chemical Engineering Journal Advances, 2022)
The prevalence of micro and nanoplastics (MNPs) across the various environments and their negative impact on ecosystems have become a serious global threat and are currently a subject of many environmental concerns. Studies have provided evidence that MNPs have the potential to leach toxic plastic chemical additives and can adsorb a variety of persistent organic environmental pollutants, thereby enhancing their bioavailability, toxicity, and dispersion. Moreover, these MNPs easily penetrate the food chain and might cause health problems when ingested by humans and other organisms. Currently, there is complexity in understanding the mechanisms by which these toxic chemicals adsorb/desorb onto/from MNPs, and the physical and biological impacts of these chemical additives. To date, there is a considerable lack of knowledge on the major chemical additives of concern used in the plastic industry, their fate once MNPs dispose into the environment, the factors that affect their degradation, and their consequent impacts on human health. This review critically analyzes the current knowledge concerning the physical, chemical, and biological impacts of MNPs, and the various chemical and organic pollutants associated with MNPs. Emphasis was laid on their types, occurrence, fate, and distribution in the environment. The different techniques used in their identification, characterization, and removal were also elucidated. Furthermore, the consequent harmful effects of MNPs on human health were discussed to spur more future studies and fill knowledge gaps in this area.